Building the Quality of Primary Education through Global Diversity to Achieve Sustainable Development Goal (SDG) 4.7 - Syaiful Rizal (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
In modern times, the impact of globalization has changed the understanding of citizenship, so that the UN through its session agreed on the Sustainable Development Goals SDGs which are contained in the 4th pillar related to education and point 7 regarding global diversity. This research uses Library Research (library study). The strategy for realizing global diversity, especially in Indonesia, in order to achieve the success of Sustainable Development Goals (SDGs) 4.7, is through an independent curriculum that achieves the Pancasila student profile. There are 4 strategies that can be implemented, especially at the Basic Education level, namely: 1) Education unit culture; Realizing Inclusive Schools, Multicultural Children's Literature, and Hidden Curriculum, 2) Intracurricular Learning; Pancasila Education and Tri Hita Karana Based Brain Based Learning Model, 3) Project for Strengthening Pancasila Student Profiles; School Policy, Group Investigation and Project Based Learning, and Extracurricular; Karawitan and Self Defense.